Shakespeare in the Capitalocene: Titus Andronicus, Timon of Athens, and Early Modern Eco-Theater. (2nd October 2018) - Gillen, Katherine
ABSTRACT: Titus Andronicus (1588) and Timon of Athens (1607) theorize what Jason W. Moore calls the Capitalocene, a world in which capitalism has reshaped the earth's materiality while also radically reconfiguring conceptions of both human and nonhuman nature. With Titus emphasizing iron weapons and Timon interrogating the force of weaponized gold, both works draw on Ovidian Iron Age mythology to show how humans have violently impacted social and natural environments and, conversely, how these transformations threaten human exceptionalism. In addition, the unusual representational strategies employed in both Titus and Timon suggest that traditional humanist aesthetics may not meet the epistemological and political exigencies of capitalogenic crisis. Ultimately, I argue, Shakespeare presents the theater, aptly named the Globe, as a microcosm of the Capitalocene — a world that humans have largely created but which nonetheless remains structured by material forces over which humans have less than total control. Rather than aestheticizing nature, Titus and Timon repurpose the matter of theatrical space, undermining assumptions about essence and representation that underlie mimesis and shocking audiences into considering their own relationships to the social, economic, and natural worlds.